Elucidating the role of selected microRNAs in attaining optimal pharmacokinetic and pharmacodynamic (PK/PD) profiles of beta-lactam antibiotics in critically ill patients with sepsis - Jamal, Janattul Ain (Faculty of Pharmacy, 2025)
Sepsis and septic shock remain among the leading causes of intensive care unit (ICU) mortality worldwide. Despite advancements in intensive care, mortality rates for sepsis hover around 30–50%, with septic shock cases seeing rates as high as 87% [1–5]. A major cornerstone of sepsis management is timely administration of effective antibiotics, particularly the beta-lactams, valued for their broad-spectrum activity and safety profile.